(untitled) (Al-Academy, 2017)
The importance of the heritage of the Iraqi heavy symbolism and connotations where contacted habits rights and beliefs from antiquity to the present, in addition to being represented with data aesthetic it is an expression philosophical concepts associated implications incentives cultural aesthetic of the content of the intellectual including contents of semantics and symbols and the dimensions of the meanings Sayings , to turn form a legacy popularly moving window to communicate worth studying its details and search function on the character and identity and origins . Where have emerged in recent years, a phenomenon characterized by inventing new designs by modernist styles that have entered into technical system design and effectiveness to its full potential until it became one of the components of the foundation in the art of design. And here lies the importance of modernity being characterized by taking it more than knowledge domain in the various and diverse intellectual bases , and when he has designed fabrics presence of modernist trends in thought and planning. Where the first chapter discusses the problem of the research to answer the following question , " Is it possible to achieve modernity symbols of heritage designs in fabrics and costumes gowns Islamic ? The aim of the research : know the design features of the vocabulary of the heritage of Iraq . , II : Trying to recruit vocabulary inherited the same meaning and significance in the designs of fabrics and fashion gowns Islamic . adopted the limits of search products Iraqi Fashion House . has dealt with the theoretical framework first topic : Attributes aesthetic elements and symbols in the legacy of Iraq , while the second modernity and technology design in fabrics and fashion gowns Islamic . , and Chapter III : measures since been identified research community , which amounted to (10) design parameter model , has reached the research sample (5) models sampled according to deliberate on the methods of application and selection criteria to achieve the goal of the research. research and reach to the most important results : 1-Adoption of designer configurations derived from the environment in which they live, characterized by simplicity in terms of the method of execution or distribution . 2 - to adopt forms of elements and vocabulary inherited style geometric axis are the complexity and simplification to represent the idea of ​​integration with functional purpose. The most important conclusions : . 1 - owning designer Iraqi aware and willing to express his ideas and requirements derived from the environment and cultural heritage , and thus creating a model expresses the identity of the community to emphasize its close connection to societ 2 - keep pace with scientific development and innovation of a new method to express the changes of modernity in the design formats . 3 - contributed to the means and the technical developments in the formulation of ideas and artistic concepts of modernity , which involved the design configuration of the fabrics in form and substance . Research has recommended an emphasis on experience on how to pick and use ways and means of art direction and layout , and proficiency that by the designer to achieve design plan , and the creation of technical staff specializes in the use of computers to carry out the variables of color and formality and repetitive in design processes on fabrics multifunctional . The proposals include research study vocabulary folklore and handicraft industries and employment in the areas of design and printed fabrics woven and knitting , and conduct a study to establish the foundations of a design to fabric designs in the light of modern developments.